Update on pollen-food allergy syndrome. (2nd June 2020) - Poncet, Pascal; Sénéchal, Hélène; Charpin, Denis
ABSTRACT: Introduction: Allergies affect 20-30% of the population and respiratory allergies are mostly due to pollen grains from anemophilous plants. One to 5% of people suffer from food allergies and clinicians report increasing numbers of pollen-food allergy syndrome (PFAS), such that the symptoms have broadened from respiratory to gastrointestinal, and even to anaphylactic shock in the presence of cofactors. Thirty to 60% of food allergies are associated with pollen allergy while the percentage of pollen allergies associated to food allergy varies according to local environment and dietary habits Areas covered: Articles published in peer-reviewed journals, covered by PubMed databank, clinical data are discussed including symptoms, diagnosis, and management. A chapter emphasizes the role of six well-known allergen families involved in PFAS: PR10 proteins, profilins, lipid transfer proteins, thaumatin-like proteins, isoflavone reductases, and β-1, 3 glucanases. The relevance in PFAS of three supplementary allergen families is presented: oleosins, polygalacturonases, and gibberellin-regulated proteins. To support the discussion a few original relevant results were added. Expert opinion: Both allergenic sources, pollen and food, are submitted to the same stressful environmental changes resulting in an increase of pathogenesis-related proteins in which numerous allergens are found. This might be responsible for the potential increase of PFAS.